Antibiotic susceptibility of potentially probiotic vaginal lactobacilli - Ocaña, Virginia Soledad (2006)
Objective. To study the antimicrobial susceptibility of six vaginal probiotic lactobacilli. Methods. The disc diffusion method in Müeller Hinton, LAPTg and MRS agars by the NCCLS (National Committee for Clinical Laboratory Standards) procedure was performed. Due to the absence of a Lactobacillus reference strains, the results were compared to those of Staphylococcus aureus ATCC29213. Minimal Inhibitory Concentration (MIC) with 21 different antibiotics in LAPTg agar and broth was also determined. Results. LAPTg and MRS agars are suitable media to study antimicrobial susceptibility of lactobacilli. However, the NCCLS procedure needs to be standardized for this genus. The MICs have shown that all Lactobacillus strains grew at concentrations above 10 μg/mL of chloramphenicol, aztreonam, norfloxacin, ciprofloxacin, ceftazidime, ceftriaxone, streptomycin and kanamycin. Four lactobacilli were sensitive to 1 μg/mL vancomycin and all of them were resistant to 1000 μg/mL of metronidazole. Sensitivity to other antibiotics depended on each particular strain. Conclusions. The NCCLS method needs to be standardized in an appropriate medium to determine the antimicrobial susceptibility of Lactobacillus. Vaginal probiotic lactobacilli do not display uniform susceptibility to antibiotics. Resistance to high concentrations of metronidazole suggests that lactobacilli could be simultaneously used with a bacterial vaginosis treatment to restore the vaginal normal flora. Copyright